Penerapan Metode Rank Order Centroid dan Additive Ratio Assessment Pada Aplikasi Rekomendasi Supplier - Ronny Addenan; Wilda Susanti (Universitas Hamzanwadi, 2021)
PT.Yanmarindo Perkasa is a company in the sale of diesel engines, generators, tooling tools and engine spare parts. Many suppliers want to distribute their goods through PT.Yanmarindo Perkasa, thus demanding the company to choose the right supplier, in order to ensure the smooth fulfillment of stock items. The process of selecting suppliers is still done manually with criteria limited to quantitative criteria, so that the process takes a long time and the results are not precise. The purpose of this study is to build a decision support system for supplier recommendations quickly and precisely in meeting the company's needs. The supplier selection process uses the Rank-Order Centroid (ROC) method in weighting the criteria and the Additive Ratio Assessment (ARAS) for ranking. ARAS value obtained is the K value that is ranked to get the best supplier by using a computerized decision support system. The application of these two methods can speed up the results of decisions, does not take a long time and the results obtained are also maximum.